Cellulose nanocrystal-based structural color thin film, and preparation method and application thereof

CN122941037APending Publication Date: 2026-10-20ZHEJIANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610905872.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

然而,现有的CNC结构色膜在高湿度环境下易出现湿态力学性能急剧下降的问题,严重限制了其产业化应用

Benefits of technology

[0027]本发明的原理:本发明先在柠檬酸的作用下进行聚乙烯醇(含羟基)和氧化淀粉(含羧基)的酯化交联制得湿强度改性剂,再在柠檬酸的作用下利用湿强度改性剂对纤维素纳米晶(表面含羟基)进行交联改性制成湿强改性纤维素纳米晶,再利用纤维素纳米晶和湿强改性纤维素纳米晶之间原本的氢键作用和静电作用在溶剂蒸发驱动下同尺度共组装形成有序层状结构的结构色薄膜。其中,酯化交联制得的湿强度改性剂可以为结构色膜提供阻挡水分子对氢键的破坏的保护层,而同尺度共组装可以增强CNC手性向列相结构的有序性,减小了客体组分对CNC自组装行为的影响,进而提高了结构色稳定性和饱和度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention discloses a structural color film based on cellulose nanocrystals, its preparation method, and its applications. The preparation method of the structural color film based on cellulose nanocrystals includes the following steps: 1) using citric acid to esterify and crosslink oxidized starch and polyvinyl alcohol to prepare a wet strength modifier; 2) using the wet strength modifier to crosslink and modify cellulose nanocrystals to prepare wet strength modified cellulose nanocrystals; 3) mixing the cellulose nanocrystal suspension and the wet strength modified cellulose nanocrystal suspension, then injecting the mixture into a mold for solvent evaporation-induced self-assembly to obtain the structural color film based on cellulose nanocrystals. The structural color film based on cellulose nanocrystals of this invention has advantages such as strong wet responsiveness, good water resistance, high strength, and environmental friendliness, making it suitable for applications in intelligent detection, flexible electronics, and green packaging. Furthermore, its preparation method is simple, the raw materials are widely available, and the production cost is low, making it suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of structural color film materials technology, specifically relating to a structural color film based on cellulose nanocrystals, its preparation method, and its application. Background Technology

[0002] Structural color films are advanced film materials that produce color entirely without relying on pigments or dyes, but solely through the scattering, interference, or diffraction of light by their physical micro-nano structures. They possess the characteristics of vibrant colors that never fade, and can also provide some functions that traditional pigment color films cannot achieve. They have a very broad application prospect in fields such as anti-counterfeiting and encryption, intelligent sensing and interaction, and high-performance displays.

[0003] Cellulose nanocrystals (CNCs) are green nanomaterials extracted from natural cellulose. They possess high crystallinity, high specific surface area, good biodegradability and biocompatibility, and can spontaneously self-assemble into chiral nematic liquid crystal structures at certain concentrations, exhibiting unique iridescent structural colors. This makes them an ideal substrate for preparing environmentally friendly photonic materials. In recent years, CNC-based structural color films have attracted widespread attention from researchers. They can induce changes in the pitch of chiral nematic liquid crystals through variations in external environmental conditions (e.g., humidity, temperature, pH), thereby achieving reversible control of structural colors (i.e., exhibiting wet-response properties). This has shown irreplaceable application value in fields such as visual sensing, intelligent actuators, information encryption, and green packaging. However, existing CNC structural color films are prone to a sharp decline in wet mechanical properties under high humidity environments, severely limiting their industrial application.

[0004] Therefore, it is of great significance to develop a CNC structured color film that combines sensitive humidity response characteristics with high water resistance stability. Summary of the Invention

[0005] The purpose of this invention is to provide a structural color thin film based on cellulose nanocrystals, its preparation method, and its application.

[0006] The technical solution adopted in this invention is: A method for preparing a structural color thin film based on cellulose nanocrystals includes the following steps: 1) Disperse oxidized starch in water and gelatinize it to make starch paste. Then mix polyvinyl alcohol solution with starch paste, add citric acid for esterification and crosslinking, and then separate and dry the product to obtain wet strength modifier. 2) Add the wet strength modifier to the cellulose nanocrystal suspension, and then add citric acid for cross-linking modification to obtain a wet strength modified cellulose nanocrystal suspension; 3) Mix the cellulose nanocrystal suspension and the wet strength modified cellulose nanocrystal suspension, and then inject the mixture into a mold for solvent evaporation-induced self-assembly to obtain a structural color film based on cellulose nanocrystals.

[0007] Preferably, the mass ratio of polyvinyl alcohol (PVA), oxidized starch (OST), and citric acid (CA) in step 1) is 1:0.2 to 1:0.005 to 0.5.

[0008] Preferably, the starch paste in step 1) has a mass fraction of 1% to 5%.

[0009] Preferably, the number-average molecular weight of the polyvinyl alcohol in step 1) is 1700 g / mol to 2000 g / mol.

[0010] Preferably, the mass fraction of the polyvinyl alcohol solution in step 1) is 1% to 5%.

[0011] Preferably, the gelatinization in step 1) is carried out at a temperature of 90°C to 100°C.

[0012] Preferably, the esterification crosslinking in step 1) is carried out at a temperature of 90℃ to 100℃ for a time of 3h to 6h.

[0013] Preferably, the mass ratio of cellulose nanocrystals, wet strength modifier, and citric acid in step 2) is 1:0.1 to 1:0.004 to 0.02.

[0014] Preferably, the cellulose nanocrystal suspension in step 2) is prepared by a method including the following steps: mixing plant fiber raw materials and sulfuric acid solution for acid hydrolysis, then adding water to terminate the reaction, then centrifuging to remove the supernatant, and then dialysis and concentration to obtain the cellulose nanocrystal suspension.

[0015] Preferably, the plant fiber raw material is at least one of wood pulp fiber, cotton fiber, and microcrystalline cellulose.

[0016] Preferably, the mass fraction of the cellulose nanocrystal suspension in step 2) is 2% to 4%.

[0017] Preferably, the cellulose nanocrystals in step 2) have a length of 90 nm to 250 nm and a diameter of 7 nm to 10 nm.

[0018] Preferably, the crosslinking modification in step 2) is carried out at a temperature of 60℃ to 80℃ for a time of 6h to 10h.

[0019] Preferably, the mass ratio of cellulose nanocrystals and wet-strength modified cellulose nanocrystals in step 3) is 1:0.1 to 9.

[0020] Preferably, the mass fraction of the cellulose nanocrystal suspension in step 3) is 2% to 4%.

[0021] Preferably, the cellulose nanocrystals in step 3) have a length of 90 nm to 250 nm and a diameter of 7 nm to 10 nm.

[0022] Preferably, the mass fraction of the wet-strength modified cellulose nanocrystal suspension in step 3) is 4% to 6%.

[0023] Preferably, the mixing in step 3) includes the following process: first stirring and dispersing for 12h to 36h, then ultrasonically dispersing for 5min to 15min.

[0024] Preferably, the solvent evaporation-induced self-assembly in step 3) is carried out at a temperature of 25°C to 40°C, and the self-assembly time is 48h to 96h.

[0025] A structural color film based on cellulose nanocrystals is prepared by the above-described method.

[0026] Applications of a cellulose nanocrystal-based structural color film as described above in the fields of intelligent detection, flexible electronics, or green packaging.

[0027] The principle of this invention: First, a wet strength modifier is prepared by esterification and crosslinking of polyvinyl alcohol (containing hydroxyl groups) and oxidized starch (containing carboxyl groups) under the action of citric acid. Then, cellulose nanocrystals (containing hydroxyl groups on their surface) are crosslinked and modified using the wet strength modifier under the action of citric acid to produce wet strength modified cellulose nanocrystals. Finally, the original hydrogen bonding and electrostatic interactions between the cellulose nanocrystals and the wet strength modified cellulose nanocrystals are utilized to co-assemble at the same scale under solvent evaporation to form an ordered layered structured color film. The wet strength modifier obtained by esterification and crosslinking provides a protective layer for the structured color film, preventing water molecules from disrupting hydrogen bonds. Co-assembly at the same scale enhances the orderliness of the chiral nematic phase structure of the CNC (carbon nanocrystal) and reduces the influence of guest components on the self-assembly behavior of the CNC, thereby improving the stability and saturation of the structured color.

[0028] The beneficial effects of this invention are: the cellulose nanocrystal-based structural color film of this invention has the advantages of strong wet responsiveness, good water resistance, high strength, and environmental friendliness, and is suitable for use in fields such as intelligent detection, flexible electronics, and green packaging. Moreover, its preparation method is simple, the raw materials are widely available, and the production cost is low, making it suitable for large-scale industrial production and application.

[0029] Specifically: 1) The main component of the cellulose nanocrystal-based structural color film of the present invention is cellulose nanocrystal. Cellulose nanocrystal is extracted from plant fiber raw materials. It not only has a wide range of raw material sources and a simple extraction process, but also has high crystallinity, high specific surface area, good biodegradability and biocompatibility, and can self-assemble to form an iridescent structural color film. 2) This invention utilizes polyvinyl alcohol, oxidized starch and citric acid crosslinking to introduce hydrophobic ester groups and flexible long chains into a cellulose nanocrystal matrix, and the resulting structural color film has the advantages of strong wet responsiveness and good water resistance. 3) The structural color film based on cellulose nanocrystals of the present invention has high wet strength and strong humidity response performance. It belongs to high-strength, environmentally friendly cellulose nanocrystal photonic materials and is suitable for large-scale industrial production and application. Attached Figure Description

[0030] Figure 1 The images shown are TEM images, XRD patterns, length distribution diagrams, and width distribution diagrams of the cellulose nanocrystals in the examples.

[0031] Figure 2 The image shows the FTIR spectrum of the wet strength modifier used in the examples.

[0032] Figure 3 The ultraviolet transmission spectra and water contact angle test diagrams of CPO-0, CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5 in Comparative Examples 1 and 3 are shown, as well as the physical image, POM image and SEM image of CPO-3 in Comparative Example 3.

[0033] Figure 4 Humidity-induced structural color response diagrams, CIE colorimetric diagrams, and water contact angle test diagrams for CC-0, CC-1, CC-2, CC-3, CC-4, CC-5, CC-6, CC-7, CC-8, CC-9, and CC-10 in Comparative Example 1, Example 2, and Comparative Example 2.

[0034] Figure 5 The graph shows the water resistance test results of CC-0, CC-2, and CPO-3 in Comparative Example 1, Example 2, and Comparative Example 3.

[0035] Figure 6 The stress-strain curves of CC-0, CC-2, and CPO-3 before and after moisture absorption are shown in Comparative Example 1, Example 2, and Comparative Example 3. Detailed Implementation

[0036] The present invention will be further explained and described below with reference to specific embodiments.

[0037] Example: A cellulose nanocrystal suspension is prepared by the following method: Oven-dried wood pulp fiber and a 64% sulfuric acid aqueous solution were mixed at a ratio of 1 g: 8.75 mL. The mixture was then heated in a constant temperature water bath at 45°C and stirred vigorously for 30 min. Ten times the volume of deionized water was added to terminate the acid hydrolysis reaction. The mixture was then centrifuged at 5000 r / min for 10 min. The supernatant was removed, and the precipitate was repeatedly washed and centrifuged with deionized water. The suspension was then placed in a dialysis bag (with a molecular weight cutoff of 8000 Da to 14000 Da) and dialyzed with deionized water until the pH of the dialysate stabilized at 7.0. The solution was then concentrated to a mass fraction of 3% using a rotary evaporator at 40°C to obtain a cellulose nanocrystal suspension (sealed and refrigerated for later use).

[0038] Performance testing: The cellulose nanocrystal suspension in this embodiment was subjected to transmission electron microscopy (TEM) and X-ray diffraction (XRD) tests. The TEM image, XRD image, length distribution map, and width distribution map of the cellulose nanocrystals are shown below. Figure 1 (a is the TEM image, b is the XRD image, c is the length distribution image, and d is the width distribution image) as shown.

[0039] Depend on Figure 1 From a, c, and d in the figure, we can see that the length of the cellulose nanocrystals is distributed in the range of 90nm to 250nm, the diameter is about 9nm, and they are rod-shaped nanocrystals with a high aspect ratio and regular morphology.

[0040] Depend on Figure 1 As shown in b, cellulose nanocrystals exhibit characteristic diffraction peaks at 2θ = 18.2° and 22.5°, and their crystallinity is calculated to be 84%.

[0041] A structural color thin film based on cellulose nanocrystals is prepared by the following method: 1) Mix 5g of polyvinyl alcohol (number average molecular weight of 1750g / mol) and 95g of deionized water, and stir at 95℃ to prepare a polyvinyl alcohol solution (mass fraction of 5%); mix 3g of oxidized starch and 97g of deionized water, and stir at 95℃ to prepare a starch paste (mass fraction of 3%); mix 100g of polyvinyl alcohol solution and 100g of starch paste (to obtain a PVA-OST mixture), and add 2g of citric acid under constant temperature of 95℃ and continue stirring for 3h. Separate and collect the lower cross-linking product, take the gel and place it in a freeze dryer to freeze dry for 36h, grind it, and obtain a wet strength modifier; 2) Mix 1g of wet strength modifier and 19g of deionized water, and stir evenly at 80°C to prepare a wet strength modifier solution; mix 2.4g of the cellulose nanocrystal suspension in this example and 0.6g of the wet strength modifier solution, with a mass ratio of cellulose nanocrystals to wet strength modifier of 2.4:1, and then add 0.1g of citric acid aqueous solution (mass fraction of 0.3%) while stirring at 60°C, continue stirring for 8 hours, and allow to cool naturally to room temperature to obtain a wet strength modified cellulose nanocrystal suspension; 3) The cellulose nanocrystal suspension and the wet-strength modified cellulose nanocrystal suspension in this embodiment were mixed. The mass ratio of cellulose nanocrystals to wet-strength modified cellulose nanocrystals was 9:1, 8:2, 7:3, 6:4, 5:5, 4:6, 3:7, 2:8 and 1:9, respectively. The mixture was stirred at room temperature (25°C) for 24 hours. Then, it was added to an ultrasonic cell disruptor and ultrasonically treated for 5 minutes under ice bath conditions. The mixture was then poured into a culture dish and evaporated and dried at 30°C to form a film, thus obtaining structural color films based on cellulose nanocrystals (referred to as CC-1, CC-2, CC-3, CC-4, CC-5, CC-6, CC-7, CC-8 and CC-9, respectively).

[0042] Performance testing: The wet strength modifier in this embodiment was subjected to Fourier transform infrared spectroscopy (FTIR) testing, and the obtained FTIR image is shown below. Figure 2 (PVA-OST mixture as a control) is shown.

[0043] Depend on Figure 2 It can be seen that the wet strength modifier is at 1712cm. -1 A distinct new peak appears nearby, which is attributed to the characteristic absorption of the carbonyl group (C=O) in the ester bond, indicating that PVA and OST undergo esterification crosslinking.

[0044] Comparative Example 1: A structural color thin film based on cellulose nanocrystals is prepared by the following method: Add 3.0g of cellulose nanocrystal suspension (same as in the example) to an ultrasonic cell disruptor and sonicate for 5 minutes under ice bath conditions. Then inject it into a culture dish and evaporate and dry it at 30°C to form a film, thus obtaining a structural color film based on cellulose nanocrystals (denoted as CPO-0 or CC-0).

[0045] Comparative Example 2: A structural color thin film based on cellulose nanocrystals is prepared by the following method: 3.0 g of wet-strength modified cellulose nanocrystal suspension (same as in the example) was added to an ultrasonic cell disruptor and ultrasonically treated for 5 min under ice bath conditions. Then it was injected into a culture dish and evaporated and dried at 30°C to form a film, thus obtaining a structural color film based on cellulose nanocrystals (denoted as CC-10).

[0046] Comparative Example 3: A structural color thin film based on cellulose nanocrystals is prepared by the following method: 1) Mix the cellulose nanocrystal suspension (same as in the example) and the wet strength modifier solution (same as in the example). The mass ratio of cellulose nanocrystals to wet strength modifier is 9:1, 8:2, 7:3, 6:4 and 5:5 respectively. Then, add 0.1g of citric acid aqueous solution (mass fraction of 0.3%) while stirring at 60°C. Continue stirring for 8 hours and let it cool naturally to room temperature to obtain a wet strength modified cellulose nanocrystal suspension. 2) The wet-strength modified cellulose nanocrystal suspension was added to an ultrasonic cell disruptor and ultrasonically treated for 5 minutes under ice bath conditions. Then it was injected into a culture dish and evaporated and dried at 30°C to form a film, thus obtaining structural color films based on cellulose nanocrystals (referred to as CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5 in sequence).

[0047] Performance testing: 1) The ultraviolet transmission spectra and water contact angle test results (testing instrument: Chengwei CW-Z101, tested according to GB / T 24368-2009 and SY / T 5153-2007 standards) of the cellulose nanocrystal-based structural color films (CPO-0, CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5) in Comparative Examples 1 and 3, as well as the physical image, polarizing microscope (POM) image and SEM image of the cellulose nanocrystal-based structural color film CPO-3 in Comparative Example 3 are shown below. Figure 3 (a shows the UV transmission spectra of CPO-0, CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5; b shows the water contact angle test results of CPO-0, CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5; c shows the physical image of CPO-3; d shows the POM image of CPO-3; e and f show the SEM images of CPO-3 at different magnifications.)

[0048] Depend on Figure 3 It can be seen that CPO-1, CPO-2, CPO-3, CPO-4 and CPO-5 still retain the chiral nematic phase structure, and the water contact angle is increased compared to CPO-0.

[0049] 2) Add 5g of deionized water to a sealed container and place it at 25℃ for 48h (to reach humidity equilibrium). Then, place the cellulose nanocrystal-based structural color films (CC-0, CC-1, CC-2, CC-3, CC-4, CC-5, CC-6, CC-7, CC-8, CC-9, and CC-10) from Comparative Example 1, Example 2, and Comparative Example 2 into petri dishes and place them in the sealed container for a moisture absorption experiment. Record the color change of the structural color films from 0min to 60min, and characterize the maximum reflection wavelength using UV-Vis transmission spectroscopy. The obtained humidity-induced structural color response diagram, CIE chromaticity diagram, and water contact angle test diagram are shown below. Figure 4 (a is the humidity-induced structural color response diagram, b is the CIE colorimetric diagram, and c is the water contact angle test diagram.)

[0050] Depend on Figure 4 It can be seen that the maximum reflection wavelength of CC-1 to CC-9 is 360nm to 560nm; CC-1 to CC-9 underwent obvious reversible structural color transformation within the relative humidity range of 30% to 100%. The CIE chromaticity diagram intuitively quantifies the adjustable range of the humidity response color of the structural color film. As the ambient humidity increases, the sample color gradually changes from blue to red, and the chromaticity coordinate span is large, indicating that the structural color film based on cellulose nanocrystals has a wide range of wet-induced color change control; at the same time, compared with CC-0, the water contact angle of CC-1 to CC-9 is significantly increased. The above data together indicate that crosslinking modification endows the structural color film with excellent humidity-responsive color development performance and controllable surface hydrophilicity.

[0051] 3) The cellulose nanocrystal-based structural color films (CC-0, CC-2, and CPO-3) from Comparative Example 1, Example 2, and Comparative Example 3 were cut into squares of 2cm × 2cm. The water contact angle was then tested and recorded using a water contact angle tester (Chengwei CW-Z101, tested according to GB / T 24368-2009 and SY / T 5153-2007 standards). The structural color films were then immersed in water and ultrasonically cleaned for 30 seconds every 10 minutes at an ultrasonic power of 80W. The appearance of the structural color films was recorded. The water resistance test results are as follows: Figure 5 As shown, the stress-strain curves before and after moisture absorption are as follows: Figure 6 (a is the stress-strain curve before moisture absorption, and b is the stress-strain curve after moisture absorption) as shown.

[0052] Depend on Figure 5 It can be seen that CC-0 gradually breaks down, while CC-2 and CPO-3 have excellent water resistance stability.

[0053] Depend on Figure 6It can be seen that the dry tensile strength of CC-2 is 45 MPa and the wet tensile strength can reach 30 MPa, which is significantly higher than the wet tensile strength of CC-0 (pure CNC film). This indicates that the PVA-OST crosslinking network restricts water molecules from breaking the hydrogen bonds inside the CNC, thereby effectively improving the wet mechanical properties of the material.

[0054] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for preparing a structurally colored thin film based on cellulose nanocrystals, characterized in that, Includes the following steps: 1) Disperse oxidized starch in water and gelatinize it to make starch paste. Then mix polyvinyl alcohol solution with starch paste, add citric acid for esterification and crosslinking, and then separate and dry the product to obtain wet strength modifier. 2) Add the wet strength modifier to the cellulose nanocrystal suspension, and then add citric acid for cross-linking modification to obtain a wet strength modified cellulose nanocrystal suspension; 3) Mix the cellulose nanocrystal suspension and the wet strength modified cellulose nanocrystal suspension, and then inject the mixture into a mold for solvent evaporation-induced self-assembly to obtain a structural color film based on cellulose nanocrystals.

2. The preparation method according to claim 1, characterized in that: The mass ratio of polyvinyl alcohol, oxidized starch, and citric acid in step 1) is 1:0.2 to 1:0.005 to 0.5; and / or the number average molecular weight of polyvinyl alcohol in step 1) is 1700 g / mol to 2000 g / mol.

3. The preparation method according to claim 1 or 2, characterized in that: The gelatinization in step 1) is carried out at a temperature of 90℃ to 100℃; and / or the esterification crosslinking in step 1) is carried out at a temperature of 90℃ to 100℃ for a time of 3h to 6h.

4. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of cellulose nanocrystals, wet strength modifier, and citric acid is 1:0.1 to 1:0.004 to 0.

02.

5. The preparation method according to claim 1 or 4, characterized in that: Step 2) The cellulose nanocrystal suspension is prepared by a method including the following steps: mixing plant fiber raw materials and sulfuric acid solution for acid hydrolysis, then adding water to terminate the reaction, then centrifuging to remove the supernatant, and then dialysis and concentration to obtain the cellulose nanocrystal suspension.

6. The preparation method according to claim 1 or 4, characterized in that: Step 2) The crosslinking modification is carried out at a temperature of 60℃~80℃ for 6h~10h.

7. The preparation method according to claim 1, characterized in that: Step 3) The mass ratio of cellulose nanocrystals to wet-strength modified cellulose nanocrystals is 1:0.1 to 9.

8. The preparation method according to claim 1 or 7, characterized in that: Step 3) The solvent evaporation-induced self-assembly is carried out at a temperature of 25℃~40℃, and the self-assembly time is 48h~96h.

9. A structural color thin film based on cellulose nanocrystals, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.

10. The application of a cellulose nanocrystal-based structural color film as described in claim 9 in the fields of intelligent detection, flexible electronics, or green packaging.